Er hægt að hafa áhrif á rannsóknarbeiðnir lækna með íhlutunum? - Helga Erlingsdóttir 1976- (2014)
Hagfræðideild hefur gefið leyfi fyrir lokuðum aðgangi að þessari ritgerð í eitt ár. Background: Physicians order laboratory tests for various reasons during diagnoses and treatments. However, laboratory tests affect health-care costs and unnesseary test requests can thus be a concern. The objective in this study is to examine whether it is possible to influence physician laboratory-test requests using four different interventions; follow-up of clinical guidelines, education, feedback and reminder letters that have occurred at different times at Landspitali University Hospital compared to Akureyri Hospital, which is used as a control as no formal interventions were implemented there. Material and Methods: Six types of laboratory tests for which clinical guidelines have been made were analysed. The average number of tests per month before and after implementation of the guidelines was compared. The relative risk of a laboratory test being conducted at Landspitali University Hospital compared to Akureyri Hospital was calculated for various points in time, as well as the associated 95% confidence intervals. The primary estimates compare the pre and post intervention periods (2007-2009 vs. 2010-2013), but also on a monthly basis in order to observe the trend over the whole period from January 2007 to July 2013 in greater detail. Results: The multifaceted interventions at Landspitali University Hospital led to a significant reduction in the average number of laboratory tests (12-52%, p<0.001) compared with Akureyri Hospital. When the relative risk coefficients of laboratory tests at Landspitali University Hospital compared to Akureyri Hospital were calculated pre and post guidelines, the relative risk for ASAT, CRP and GGT fell markedly, while ALAT and ALP tests did not show a significant decrease. Relative risk for a blood culture test in the period after the guidelines was statistically significantly increased. Conclusion: It is possible to influence physician laboratory-test requests using multifaceted ...